Characterization, modeling and design of the braided pneumatic muscle - Doumit, Marc D (University of Ottawa (Canada), 2009)
Electrical motors, hydraulic and pneumatic cylinders are traditionally used as actuators. They are very effective for most industrial applications; however, they are not suitable for devices that interact with human beings. Such devices can be medical assisting robots, robotic prostheses for handicapped people and others. To ensure the safety of the user (i.e. patient) and the effectiveness of the device, these applications require an actuator that is compliant and physically flexible, yet powerful and of light weight. The Braided Pneumatic Muscle, a pneumatic linear actuator, is a candidate device that satisfies the above requirements. Although invented in 1941, limited experimental evaluation of the BPM has hindered its applicability until 1961. Moreover, accurate mechanical models and design processes, as well as the issues of proper control of the device, still limits its wide spread application. This thesis aims to study the Braided Pneumatic Muscle behaviour, develop mechanical models to characterize this as well as to propose a design process that enables the user to select the Braided Pneumatic Muscle size and configuration based on the required muscle force, the muscle contraction distance and the muscle stiffness. In this thesis, a comprehensive experimental evaluation is achieved which led to the discovery of new muscle properties as well as the understanding of muscle behaviour. Moreover, a novel force-based modeling approach has been developed and has resulted in accuracies of the static and dynamic models that are better than those of published analytical models. Furthermore, the muscle's dynamic behaviour has been modeled using linear and non-linear system identification models. Finally, the closed loop behaviour of the Braided Pneumatic Muscle was analyzed with a Proportional Integral Derivative controller.
Keywords: Engineering, Mechanical.